Kebijakan Moneter di Negara Islam dan Negara Muslim: Iran, Pakistan, Saudi Arabia, dan Indonesia - Aziz, Riva Abdillah (TAWAZUN: Journal of Sharia Economic Law, 2023)
Monetary policy is a policy issued by a central bank or institution that is authorized with the aim of which is to maintain and stabilizing the currency so that the country's economy does not fall, that it can also be used as a regulation for setting interest rates and controlling the amount of money in circulation. Macroeconomic stability is the main goal of monetary policy. Currently, there are two economic systems operating in the world, namely conventional and sharia-based economic systems. These two bases of the economic system inevitably also influence monetary policy. This article discusses how monetary policy applies to Islamic and Muslim countries. The research method used in writing this article is qualitative, while the approach used is descriptive. The type of research used is Library (Library Research). The final result of this article concludes that: Islamic countries which use sharia (Islam) principles in their daily lives cannot be separated from the sharia economic system, this is because these countries are bound by international transactions, which ultimately these countries issued conventional monetary policies to adapt to international transactions.